Bongkrekic Acid Analogue, Lacking One of the Carboxylic Groups of its Parent Compound, Shows Moderate but pH‐insensitive Inhibitory Effects on the Mitochondrial ADP/ATP Carrier. (13th June 2015) - Yamamoto, Atsushi; Hasui, Keisuke; Matsuo, Hiroshi; Okuda, Katsuhiro; Abe, Masato; Matsumoto, Kenji; Harada, Kazuki; Yoshimura, Yuya; Yamamoto, Takenori; Ohkura, Kazuto; Shindo, Mitsuru; Shinohara, Yasuo
Abstract : Bongkrekic acid, isolated from Burkholderia cocovenenans, is known to specifically inhibit the mitochondrial ADP/ATP carrier. However, the manner of its interaction with the carrier remains elusive. In this study, we tested the inhibitory effects of 17 bongkrekic acid analogues, derived from the intermediates obtained during its total synthesis, on the mitochondrial ATP/ATP carrier. Rough screening of these chemicals, performed by measuring their inhibitory effects on the mitochondrial ATP synthesis, revealed that 4 of them, KH‐1, KH‐7, KH‐16, and KH‐17, had moderate inhibitory effects. Further characterization of the actions of these 4 analogues on mitochondrial function showed that KH‐16 had moderate; KH‐1 and KH‐17, weak; and KH‐7, negligible side effects of both permeabilization of the mitochondrial inner membrane and inhibition of the electron transport, indicating that only KH‐7 had a specific inhibitory effect on the mitochondrial ADP/ATP carrier. Although the parental bongkrekic acid showed a strong pH dependency of its action, the inhibitory effect of KH‐7 was almost insensitive to the pH of the reaction medium, indicating the importance of the 3 carboxyl groups of bongkrekic acid for its pH‐dependent action. A direct inhibitory effect of KH‐7 on the mitochondrial ADP/ATP carrier was also clearly demonstrated. Abstract : Inhibitory effects of 17 bongkrekic acid analogues derived from the intermediates obtained during its total synthesis, on the mitochondrial ATP/ATP carrier were examined. One compound, KH‐7, lacking one of the carboxylic groups of its parent compound, showed moderate but pH‐intensive inhibitory effects on the mitochondrial ADP/ATP carrier.